SIMPLE VS SOPHISTICATED EPISTEMIC BELIEFS AN INITIAL STEP TO DEVELOP SEMINAR ON ELT COURSE MATERIAL - Ressi Delijar; Ive Emaliana (JURNAL ILMIAH BAHASA DAN SASTRA, 2021)
The development of appropriate teaching materials not only needs to be adjusted to the latest curriculum but also to the needs of the parties involved in learning. One of the parties involved is the learner. The needs of learners in the learning process must be known in order to develop appropriate teaching materials. This study is intended to map the needs of learners in the Seminar on ELT class as a first step to develop appropriate teaching materials by considering the different characteristics of students through the perspective of their epistemological beliefs. The participants involved in this study were 102 students who had attended the Seminar on ELT class. The result showed that majority of Seminar on ELT students (95%) are having sophisticated epistemic beliefs which we can describe them as the students that believe the knowledge is always changing or tentative, learning can be done individually by everyone, their knowledge of English did not come from authority, but through reason or logic experiences. They also believe that everyone can learn English from the beginning, no matter what age, or even their background. They agree on process-oriented learning. They also tend to have high motivation to learn English regardless of whether the motivation is extrinsic or intrinsic motivation. With this finding, we can finally understand the characteristics of the Seminar on ELT students as an initial step to develop an appropriate course material. Keywords: Epistemic Beliefs, Needs Analysis, Course Material Development, ELT